Pre-arrest diversion to addiction treatment by law enforcement: protocol for the community-level policing initiative to reduce addiction-related harm, including crime - Aleksandra E. Zgierska; Veronica M. White; Joseph Balles; Cory Nelson; Jason Freedman; Thao H. Nguyen; Sarah C. Johnson (BMC, 2021)
Abstract Background Despite evidence that treatment reduces addiction-related harms, including crime and overdose, only a minority of addiction-affected individuals receive it. Linking individuals who committed an addiction-related crime to addiction treatment could improve outcomes. Methods The aim of this city-wide, pre-arrest diversion program, Madison Addiction Recovery Initiative (MARI) is to reduce crime and improve health (i.e., reduce the overdose deaths) among adults who committed a minor, non-violent, drug use-related offense by offering them a referral to treatment in lieu of arrest and prosecution of criminal charges. This manuscript outlines the protocol and methods for the MARI program development and implementation. MARI requires its participants to engage in the recommended treatment, without reoffending, during the six-month program, after which the initial criminal charges are "voided" by the law enforcement agency. The project, implemented in a mid-size U.S. city, has involved numerous partners, including law enforcement, criminal justice, public health, and academia. It includes training of the police officer workforce and collaboration with clinical partners for treatment need assessment, treatment placement, and peer support. Program evaluation includes formative, process, outcome (participant-level) and exploratory impact (community-level) assessments. For outcome evaluation, we will compare crime (primary outcome), overdose-related offenses, and incarceration-related data 12 months before and 12 months after the index crime between participants who completed (Group 1), started but not completed (Group 2), and were offered but did not start (Group 3) the program, and adults who would have been eligible should MARI existed (Historical Comparison, Group 4). Clinical characteristics will be compared at baseline between Groups 1-2, and pre-post the program within Group 1. Participant baseline data will be assessed as potential covariates. Surveys of police officers and program completers, and community-level indicators of crime and overdose pre- versus post-program will provide additional data on the program impact. Discussion By offering addiction treatment in lieu of arrest and prosecution of criminal charges, this pre-arrest diversion program has the potential to disrupt the cycle of crime, reduce the likelihood of future offenses, and promote public health and safety.